2007
DOI: 10.1371/journal.pone.0000730
|View full text |Cite
|
Sign up to set email alerts
|

Differential Drug Resistance Acquisition in HIV-1 of Subtypes B and C

Abstract: BackgroundSubtype C is the most prevalent HIV-1 subtype in the world, mainly in countries with the highest HIV prevalence. However, few studies have evaluated the impact of antiretroviral therapy on this subtype. In southern Brazil, the first developing country to offer free and universal treatment, subtypes B and C co-circulate with equal prevalence, allowing for an extensive evaluation of this issue.Methods and FindingsViral RNA of 160 HIV-1+ patients was extracted, and the protease and reverse transcriptase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 34 publications
3
51
1
1
Order By: Relevance
“…51 In a study of patients from Rio Grande do Sul, Brazil, in a population infected by subtypes B and C, a lower rate of accumulation of mutations was found in subtype C than subtype B. 52 However, certain NRTI mutations such as K65R have been shown to develop more quickly in subtype C than in other subtypes. 13 NNRTI-associated mutations were found in 98.5% of patients in virologic failure.…”
Section: Hiv-1 Subtype On Drug Resistance Mutations In Nigeriamentioning
confidence: 99%
“…51 In a study of patients from Rio Grande do Sul, Brazil, in a population infected by subtypes B and C, a lower rate of accumulation of mutations was found in subtype C than subtype B. 52 However, certain NRTI mutations such as K65R have been shown to develop more quickly in subtype C than in other subtypes. 13 NNRTI-associated mutations were found in 98.5% of patients in virologic failure.…”
Section: Hiv-1 Subtype On Drug Resistance Mutations In Nigeriamentioning
confidence: 99%
“…Brenner et al (3) have shown for subtype C that the 65R mutation occurs faster in cell culture in response to tenofovir pressure than it does in subtype B. A study from Brazil looked at 160 sequences from treatment-experienced HIV-1-infected individuals (21). It was found that subtype C viruses accumulated drug resistance mutations at a lower rate than subtype B isolates after at least 4 years of treatment.…”
mentioning
confidence: 99%
“…The same study showed that the 41L mutation was rare compared to what was expected from the subtype B data; in fact, it did not occur in this study at all. In Brazil, where subtypes B and C cocirculate in the same population, a study found that the 41L and 210W TAM mutations occurred more frequently in subtype B than in subtype C (21).…”
mentioning
confidence: 99%
“…Of these, group M, which is responsible for the majority of infections worldwide, is further subdivided into 9 subtypes or clades (subtypes A to K) (63). Previous reports (46,(64)(65)(66) suggested that there are differences between subtypes B and C in the accessory genes, leading to specific differences in their abilities to carry out a particular function. Hence, we were interested to see if there is any such difference with respect to inhibition of whole-cell ubiquitination by Vpr.…”
Section: Discussionmentioning
confidence: 99%